The Set-Point Theory of Well-Being Needs Replacing: On the Brink of a Scientific Revolution? - Bruce Headey (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
Set-point theory has dominated the field of subjective well-being (SWB). It has served as a classic Kuhn research paradigm, being extended and refined for thirty years totake in new results. The central plank of the theory is that adult set-points do not change, except just temporarily in the face of major life events. There was always some "discordant data", including evidence that some events are so tragic (e.g. the death of one's child) that people never recover back to their set-point. It was possible to dismiss these events as "exceptions" and maintain the theory. However, several new findings are now emerging, which it is increasingly difficult to dismiss as "exceptions" and which appear to require substantial revisions or replacement of set-point theory. Many of these findings are based on data from the German Socio-Economic Panel Survey (SOEP, 1984 - ) which provides clear evidence of large, long term changes in the set-points of substantial minorities of the population. This paper reviews recent findings and highlights lines of theory development which, at minimum, represent substantial revisions to set-point theory and which may perhaps lead to replacement of the paradigm. There is evidence to suggest that individuals with certain personality traits are more likely to record long term change in SWB than others. Also, SWB appears to depend partly on choice/prioritisation of some life goals rather than others. Pursuit of non-zero sum goals (family and altruistic goals) leads to higher SWB than pursuit of zero sum goals (career advancement and material gains). Both these new lines of theory appear promising and the second, in particular, cannot sensibly be reconciled with set-point theory.
Keywords: 330